Penerapan Pendekatan Interaktif oleh Tutor dalam Pembelajaran Paket C Pada Kelompok Binuang Sakti Kota Padang - Ciptro Hadrianto (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2013)
The writing of this article aims to describe the application of an interactive approach by tutors in the Binuang Sakti in package C Group SKB Region I of Padang on aspects: (1) formulation of objectives, (2) the presentation of the material, (3) methods, and (4) evaluation of learning. Type of research is descriptive quantitative study involving 30 respondents. Data collection techniques by distributing questionnaires to each respondent according to their content of each other's opinions. Once the data is analyzed by the authors view using the percentage formula. The study findings suggest that interactive approaches undertaken in Group C tutor package Binuang Sakti in SKB Region I of Padang has been good. This is evidenced by the percentage of respondents who chose either the ability of tutors to apply an interactive approach is very high. It can be concluded almost all respondents said that tutors have been able to apply an interactive approach in formulation objectives, the presentation of the material, methods has used, and evaluation of learning are good.